Elective Hospitalizations for Intractable Headache: Outcomes and Response Predictors. Issue 3 (June 2021) - Kiarashi, Jessica; Jion, Yasmin; Giglio, Brandon; Pavlovic, Jelena; Armand, Cynthia E.; Grosberg, Brian M.; Lipton, Richard B.; Vollbracht, Sarah; Robbins, Matthew S.
Abstract : Objective: To review our inpatient experience treating a variety of headache disorders with heterogeneous therapies and to determine outcomes and predictors of response. Methods: We conducted an institutional review board–approved retrospective chart review of elective inpatient headache admissions from the Montefiore Headache Center from 2014 to 2018. We examined factors associated with response and outcomes at discharge and posthospitalization follow-up in an intractable population. Patients received different classes of IV medications including antiemetics, neuroleptics, dihydroergotamine, lidocaine, steroids, valproic acid, and nerve blocks, and home preventive medications were either continued or changed before discharge. Improvements were defined at discharge by headache intensity compared with before hospitalization. Results: Among the 83 admissions, pain improvement at discharge occurred in 90.4% (n = 75) of the overall sample, 89.5% (n = 60) of those with chronic migraine, 75.0% (n = 9) of patients with new daily persistent headache, and 89.5% (n = 34) of all those with acute medication overuse. Fifty-six patients (67.5%) reported improvement of a 3-or-more-point reduction in headache intensity at discharge, with a mean reduction of 4.84 ± SD 2.51 (range 1–10). Of the 66 patients who received IV dihydroergotamine, 59 (89.4%) of them improved at discharge. Of the 11 (13.2%) patients who received IV lidocaine, 7 (63.6%) improved. Of the 14 (16.9%) patients who received nerve blocks, all 14 (100%) improved at discharge. Of the 75 patients who had improved at discharge, 63 (84%) followed up and 50 (79.4%) of those patients remained improved. At the second follow-up, 68 (81.9%) patients returned for follow-up on average of 71 days (range 10–283) after discharge. Conclusions: Our inpatient headache experience featured numerous treatments with high rates of improvement in the short and intermediate term for all headache disorders. These results may suggest that stratified hospitalized care including polytherapy may be useful for many patients.